Evolving farmer requirements for rice varieties in Indonesia - Connor, Melanie; Malabayabas, Arelene Julia B.; Herta Novalina Sipayung; Devanda Ayu Lidya Permata Putri; Fadlan Solichin; Nuning Agrosubekti; Arlyna Budi Pustika; Sudarmaji; Hasil Sembiring (CGIAR, 2024)
For many years, Indonesia relied on high-input use to maintain yields with low-yielding varieties. Farmers’ demand for high-yielding varieties was met through participatory action research, which introduced new high-yielding varieties in combination with best agronomic practices in Yogyakarta, Java, one of the main rice-growing regions in Indonesia. The present brief evaluates the changing varietal requirements in Indonesia. The Closing Rice Yield Gap in Asia (CORIGAP) Project provides a case study of how new requirements for high-yielding varieties took hold. In addition, evolving farmer requirements were evaluated through the Market Intelligence Initiative. Data were obtained from three longitudinal surveys and also interviews with 20 farmers investigating current and future varietal needs. Results show farmers switching from low-yielding varieties (e.g., IR 64 and Ciherang) to high-yielding ones (e.g., Inpari 42 and 43). This turnover was accompanied by changing agronomic practices—in particular, nutrient and rodent management promoted during the project. The interviews show that farmers use direct seeding as crop establishment and production takes place in tidal-swamp areas in other parts of Indonesia. Neither direct-seeding nor tidals wamp areas are currently included in the market segmentation. Production in tidal swamps has the capacity to increase the size of the rice-growing area 45 times, to 9.9 million ha. While farmers currently grow high-yielding varieties, these varieties are not suitable for tidal swamp areas; farmers require varieties that are adapted to this ecological zone—a market segment not currently defined. Furthermore, climate change is causing extensive droughts. Drought resistance is new to Indonesia, which traditionally suffers more from floods, requiring that it be incorporated into the current TPPs to reduce yield loss due to extended drought periods during the dry season.